2004
DOI: 10.1292/jvms.66.1119
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Activities of Cytosolic Phospholipase A2 and Arachidonic Acid-Metabolizing Enzymes in Di-(2-Ethylhexyl)Phthalate-Induced Testicular Atrophy

Abstract: ABSTRACT. Di-(2-ethylhexyl) phthalate (DEHP), a peroxisome proliferator-activated receptor α (PPARα) ligand, alters the lipid composition of rat testis, yet the mechanism is unclear. In this study, we investigated the effect of DEHP on the synthesis and metabolism of arachidonic acid (AA), a precursor of eicosanoids, in the testis of prepubertal rats. DEHP (100 and 1,000 mg/kg, 5 days) admini stration caused a significant reduction in activity of cytosolic phospholipase A 2 (cPLA 2 ), the rate-limiting enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…They mediate the metabolism of long chain EFAs to eicosanoids, which can be further converted to other important bioactive molecules critical for fetal development, such as PG, thromboxane and prostacyclin [26]. The current study demonstrated that the expression of CYP4A1, the major CYP4A isoform present in rat placenta [12], was significantly induced in both the LAB and JXN (Figure 3), consistent with previous reports in mouse liver [27] and testis [28]. The induction pattern of CYP4A1 correlated with the observed changes of PPARα by DEHP exposure (Figure 1), which might reflect the fact that CYP4A isoforms are under transcriptional control of PPARs, particularly PPARα [29].…”
Section: Discussionsupporting
confidence: 91%
“…They mediate the metabolism of long chain EFAs to eicosanoids, which can be further converted to other important bioactive molecules critical for fetal development, such as PG, thromboxane and prostacyclin [26]. The current study demonstrated that the expression of CYP4A1, the major CYP4A isoform present in rat placenta [12], was significantly induced in both the LAB and JXN (Figure 3), consistent with previous reports in mouse liver [27] and testis [28]. The induction pattern of CYP4A1 correlated with the observed changes of PPARα by DEHP exposure (Figure 1), which might reflect the fact that CYP4A isoforms are under transcriptional control of PPARs, particularly PPARα [29].…”
Section: Discussionsupporting
confidence: 91%
“…There are four major classes of phospholipase, termed A, B, C, and D, those are distinguished by the type of reaction that they catalyze. A previous study showed that DEHP (100 and 1,000 mg/kg, 5 days) administration caused a significant reduction in the activity of cytosolic PLA in the testes of prepubertal rats (Kim et al, ). In our study, the expression of PLA was down‐regulated at both the mRNA and protein levels in male mice after combined treatment with DEHP and Aroclor 1254.…”
Section: Discussionmentioning
confidence: 98%
“…Using our approach, several proteins were identified as being associated with DEHP (Table 2). Cysteine dioxygenase type I (CD01) and peroxisome proliferator-activated receptor alpha (PPARA), the two top scoring proteins, are already known in the CTD and from the literature [37][38] as molecular targets for DEHP. Six other high ranking proteins are new potential DEHP molecular targets which are not recorded in the CTD (thus not input data).…”
Section: Resultsmentioning
confidence: 99%